Field-amplified sample injection and in-capillary derivatization for capillary electrophoretic analysis of metal ions in local wines - Santalad A. (2014)
In-capillary derivatization and field-amplified sample injection (FASI) coupled to capillary zone electrophoresis (CZE) was evaluated for the analysis of metals (Co(II), Cu(II), Ni(II), and Fe(II)) using 2-(5-Nitro-2-Pyridylazo)-5-(N-Propyl-N-Sulfopropylamino)Phenol (Nitro-PAPS) as the derivatizing agent. For FASI, the optimum conditions were water as sample solvent, 1 s hydrodynamic injection (0.1 psi) of a water plug, 5 s of electrokinetic introduction (10 kV) of the sample. The in-capillary derivatization was successfully achieved with zone-passing strategy in order tandem injection of Nitro-PAPS reagent (0.5 psi, 7 s), a small water plug (0.1 psi, 1 s), and metal ion introduction (10 kV, 5 s). The solution of 45 mmol L- 1 borate pH 9.7 and 1.0 × 10- 5 mol L- 1 Nitro-PAPS containing 20% acetonitrile was used as the running buffer. The limit of detection obtained by the proposed method was lower than those from pre-capillary derivatization about 3-28 times. The recovery of the method was comparable to pre-capillary derivatization method. In-capillary derivatization-FASI-CZE was applied to analysis of metals in wine samples. The results were compared with those obtained by CZE with pre-capillary derivatization method and atomic absorption spectrometry (AAS). © 2007 Elsevier B.V. All rights reserved.